Ethyl acetate extract of Knoxia roxburghii (Rubiaceae) down-regulates ECHDC1, CAMK2D, DDB1, UBA6, BIRC6, and HK1 proteins and ameliorates the symptoms of diabetes mellitus - Wang, Xinge; Tian, Xiaoqiao; Xu, Yang; Li, Rong; Qumo, Gusha; Li, Jingping; Bao, Niman; Li, Maoru; Qiu, Bin (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the effects of Knoxia roxburghii on blood glucose levels in diabetic rats and to investigate its underlying mechanisms of action using proteomics and metabolomics.MethodsStreptozotocin (STZ)-induced diabetic rats were treated with different doses of K. roxburghii extract. Proteomics and metabolomics analyses were performed using pancreatic proteins and serum samples, and the proteomics findings were validated via parallel reaction monitoring (PRM).ResultsCompared with the model group, rats in the treatment group showed improved diabetic symptoms. Fasting blood glucose (FBG), glycated serum protein (GSP), pancreatic malondialdehyde (MDA), and the area under the curve of oral glucose tolerance test (OGTT-AUC) were significantly decreased (P < 0.01, P < 0.05), while superoxide dismutase (SOD), homeostasis model assessment of β-cell function (HOMA-β), and fasting insulin (FINS) were significantly increased (P < 0.01, P < 0.05). Histological analysis revealed an increased pancreatic islet cell area in the treatment group. Proteomic analysis identified six significantly downregulated proteins validated by PRM: Ethylmalonyl-CoA Decarboxylase 1 (ECHDC1), Calcium - Dependent Protein Kinase II Delta (CAMK2D), DNA Damage - Binding Protein 1 (DDB1), Ubiquitin-Like Modifier-Activating Enzyme 6(UBA6), Baculoviral IAP Repeat - Containing Protein6(BIRC6), and Hexokinase 1(HK1). These proteins were associated with six key metabolic pathways, including butyric acid metabolism, propionic acid metabolism, and the mTOR signaling pathway.ConclusionThe ethyl acetate extract of K. roxburghii reduces endogenous glucose production by inhibiting gluconeogenesis, alleviates oxidative stress in pancreatic cells, and preserves pancreatic islet architecture. These effects contribute to increased insulin secretion, improved glycemic control, and alleviation of diabetic symptoms in STZ-induced rats. These findings not only provide mechanistic insights into the ethnopharmacological basis for the traditional use of K. roxburghii in diabetes management, but also establish a scientific rationale supporting its clinical application through the regulation of hepatic gluconeogenesis and pancreatic β-cell preservation.